2020
DOI: 10.1111/epi.16662
|View full text |Cite
|
Sign up to set email alerts
|

Convulsive seizures and some behavioral comorbidities are uncoupled in the Scn1aA1783V Dravet syndrome mouse model

Abstract: Objective: Dravet syndrome (Dravet) is a severe childhood epileptic encephalopathy. The disease begins with a febrile stage, characterized by febrile seizures with otherwise normal development. Progression to the worsening stage features recurrent intractable seizures and the presentation of additional nonepileptic comorbidities, including global developmental delay, hyperactivity, and motor deficits. Later in life, at the stabilization stage, seizure burden decreases, whereas Dravet-associated comorbidities p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 50 publications
10
56
0
1
Order By: Relevance
“…Accordingly, a DS mouse model carrying the Scn1a A1783V missense mutation showed that low EEG power correlates with the risk of premature death during the worsening stage of DS. 30 Thus, these findings not only characterise the stage 2 of DS in F1.Scn1a(+/-) tm1kea mice but also reinforce that a severe GTCS and low background EEG power may be an immediate risk factor for SUDEP in DS mice.…”
Section: Discussionsupporting
confidence: 61%
“…Accordingly, a DS mouse model carrying the Scn1a A1783V missense mutation showed that low EEG power correlates with the risk of premature death during the worsening stage of DS. 30 Thus, these findings not only characterise the stage 2 of DS in F1.Scn1a(+/-) tm1kea mice but also reinforce that a severe GTCS and low background EEG power may be an immediate risk factor for SUDEP in DS mice.…”
Section: Discussionsupporting
confidence: 61%
“…More recently, other reports suggested that developmental delay may be independent of epilepsy 41 , 42 and subtle developmental changes have been described during the febrile stage 43 , 44 . In line with this, a recent study showed that in DS mice motor impairment and hyperactivity are evident already in the febrile stage (P14-P18) while deficits in working memory emerged during the worsening stage (P21-P27) 45 . While in our model we did not detect any motor alteration at the age of analysis (3–4 months), hyperactivity, and cognitive deficits were evident and Na v 1.1 reactivation at P30 was sufficient to rescue them.…”
Section: Discussionsupporting
confidence: 54%
“…Evaluation in the open field showed Scn1a A1783V/WT mice had significantly increased hyperactivity and anxiety-like behavior compared to wild type littermates and had poor nest building performance ( Figure 1 ). This has also been shown by others investigating the Scn1a A1783V/WT mice(17, 23) and in the Scn1a RX/+ and the Scn1a tm1Kea mouse models(15, 16, 18). Poor nest building behavior is an early predictor of behavioral deficits and is an indicator of impaired activities of daily living(24).…”
Section: Discussionsupporting
confidence: 77%